Safety and feasibility of intrastromal injection of cultivated human corneal stromal keratocytes as cell-based therapy for corneal opacities - Yam, Gary Hin-Fai (2019)
Purpose: To evaluate the safety and feasibility of intrastromal injection of human corneal stromal keratocytes (CSKs) and its therapeutic effect on a rodent early corneal opacity model. Methods: Twelve research-grade donor corneas were used in primary culture to generate quiescent CSKs and activated stromal fibroblasts (SFs). Single and repeated intrastromal injections of 2 to 4 × 104 cells to rat normal corneas (n = 52) or corneas with early opacities induced by irregular phototherapeutic keratectomy (n = 16) were performed, followed by weekly examination of corneal response under slit-lamp biomicroscopy and in vivo confocal microscopy with evaluation of haze level and stromal reflectivity, and corneal thickness using anterior segment optical coherence tomography (AS-OCT). Time-lapse tracing of Molday ION–labelled cells was conducted using Spectralis OCT and label intensity was measured. Corneas were collected at time intervals for marker expression by immunofluorescence, cell viability, and apoptosis assays. Results: Injected CSKs showed proper marker expression with negligible SF-related features and inflammation, hence maintaining corneal clarity and stability. The time-dependent loss of injected cells was recovered by repeated injection, achieving an extended expression of human proteoglycans inside rat stroma. In the early corneal opacity model, intrastromal CSK injection reduced stromal reflectivity and thickness, resulting in recovery of corneal clarity, whereas noninjected corneas were thicker and had haze progression. Conclusions: We demonstrated the safety, feasibility, and therapeutic efficacy of intrastromal CSK injection. The cultivated CSKs can be a reliable cell source for potential cell-based therapy for corneal opacities.